Reduciranje simpleksne tabele splošne metode simpleksov - Damij, Talib (Informatica (Ljubljana), 1985)
The general simplex method is known as a simple and fast iterative process but it is also known as a big computer storage consumer. In our paper we describe the necessary modifications of this method which enable us to reduce the size of simplex tableau to the size of the input matrix of the set of linear unequations.
Keywords: linearno programiranje; matematika; metoda simpleksov; operacijsko raziskovanje; reduciranje simpleksne tabele